INTEGRASI TEKNOLOGI RADIO FREQUENCY IDENTIFIKCATION DENGAN BIOSENSOR - Pamungkas Daud; Olly Vertus (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2008)
Radio Frequency Identification System can be used for every application in automatic identification machines. This issue told about Radio Frequency Identification technology combined with biosensor for identification pathogen bacterial which live in some foods. Integrated detection for disease caused by foods with wireless technology and biosensor were the main aim from this research.The end of the result was the system which can monitoring the food production process from the beginning till the end and this system can reduced the number of death caused by pathogen bacterial such as Salmonella and E Coli.Key Words: Radio,Frequency,Biosensor